2021
DOI: 10.1088/1742-6596/1793/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

The role of facilitating condition in enhancing user’s continuance intention

Abstract: Many organizations are moving toward utilizing information system to enhance eficiency in everyday task. Although the influence of facilitating condition are important to the success of information system implementation, the literature lacks empirical research on tthe relationship between facilitating condition and continuance intention in private higher leaning institution. In this article, the researchers introduce a simple model based on information systems (IS) and user behavior literature to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In the quest to provide a holistic approach towards ensuring the success of the mlearning application in the institution, the developers should also consider the availability of the application in all operating systems (OS) or platforms (e.g., iOS). Although this reflects the factor of facilitating condition, which was discovered as insignificant in this study, earlier studies of technology acceptance by Seethamraju et al (2018) and technology continuance use by Kamarozaman and Razak (2021) demonstrated its importance.…”
Section: Contributionsmentioning
confidence: 51%
See 1 more Smart Citation
“…In the quest to provide a holistic approach towards ensuring the success of the mlearning application in the institution, the developers should also consider the availability of the application in all operating systems (OS) or platforms (e.g., iOS). Although this reflects the factor of facilitating condition, which was discovered as insignificant in this study, earlier studies of technology acceptance by Seethamraju et al (2018) and technology continuance use by Kamarozaman and Razak (2021) demonstrated its importance.…”
Section: Contributionsmentioning
confidence: 51%
“…Previously, Nysveen and Pedersen ( 2016) stated that a consumer who has access to a favourable set of facilitating conditions is more likely to have a greater intention to use technology. Furthermore, a recent study by Kamarozaman and Razak (2021) related to e-campus continuance use intention found that facilitating condition plays an essential contributor. Therefore, the formation of the seventh hypothesis is based on the more facilitation conditions associated with using the gamified mlearning application, the more a user will continue to use them.…”
Section: H3: Perceived Enjoyment (Penj) Has a Positive Effect On Gami...mentioning
confidence: 99%
“…The responses suggest that the adoption of AI technologies in the Serbian hotel industry has the potential to significantly contribute to sustainability goals. By streamlining operations, optimizing resource utilization, and enhancing service delivery, AI can help hotels minimize waste, reduce energy consumption, and mitigate their environmental impact [112][113][114][115][116]. Moreover, AI-driven analytics and predictive modeling can facilitate data-driven decision-making, leading to more efficient resource allocation and improved environmental stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Also, facilitating conditions significantly impact students' intention to interact with one another (Wut et al, 2022). While the influence of facilitating conditions on the success of information system implementation is crucial, there is a lack of empirical research in the literature concerning the relationship between facilitating conditions and continuance intention in private higher learning institutions (Kamarozaman & Razak, 2021). Furthermore, the predictive role of facilitating conditions, perceived ease of use, and perceived usefulness in Iranian EFL learners' perceptions of mobile-assisted language learning (MALL) were examined by Ebadi and Raygan (2023).…”
Section: Facilitating Conditionsmentioning
confidence: 99%